1993
DOI: 10.1111/j.2044-8279.1993.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive style and mode of presentation on learning performance

Abstract: The effect of text-plus-text versus text-plus-picture computer presentation conditions, and the students' cognitive styles, on learning performance was investigated. In the text-plus-text condition, the learning material content described the working of car braking systems. The text-plus-picture condition consisted of text with additional pictorial information. Fifty-nine 15-16-year-old students in a secondary school were randomly assigned, within sexes, to one of the conditions. Having worked through the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 8 publications
6
87
2
5
Order By: Relevance
“…Höffler, Prechtl, and Nerdel (2010) found learning differences on cognitive style between ‘highly developed visualizers’ and ‘less developed visualizers’ in that the former had better learning results when using static pictures instead of animations while for the latter it made no difference. Riding and Douglas (1993) could also identify an ATI effect when confronting visualizers and verbalizers with either text plus pictures or text plus text: Visualizers performed better with the text‐plus‐pictures condition, whereas verbalizers were better with the text‐plus‐text condition.…”
Section: Introductionmentioning
confidence: 99%
“…Höffler, Prechtl, and Nerdel (2010) found learning differences on cognitive style between ‘highly developed visualizers’ and ‘less developed visualizers’ in that the former had better learning results when using static pictures instead of animations while for the latter it made no difference. Riding and Douglas (1993) could also identify an ATI effect when confronting visualizers and verbalizers with either text plus pictures or text plus text: Visualizers performed better with the text‐plus‐pictures condition, whereas verbalizers were better with the text‐plus‐text condition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while it was hypothesised that the same themes that emerged in the study by Neumann et al (2008) would also be found, it was also expected that additional themes relevant to student learning would be identified. Several processes have been suggested to be important in technology based learning, including information processing learning processes (González & Birch, 2000), visual learning (Davis & Bostrom, 1992;Psotka, Kerst & Westernman, 1993), cognitive style (Carlson, 1991;Riding & Douglas, 1993), communication (Kuehn, 1994), self-efficacy (Ertmer, Evenbeck, Cennamo & Lehman, 1994), and motivation (Lens, 1994). As such, it was hypothesised that some of these themes would also emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1970s there has been an increased focus on the applicability of learning styles research for learners in a range of educational settings, thus broadening the scope of research on individual differences. In the present study we distinguish between the cognitive-perceptual styles research (eg., Riding, 1991;Riding & Douglas, 1993) and the learning centered tradition which focuses on approaches to studying (eg., Biggs, 1987;Watkins, 1998). Each of these strands will be discussed in relation to its contribution to designing learning materials.…”
Section: Learning Styles: Categories Concepts and Frameworkmentioning
confidence: 99%